Function of Arabidopsis CPL1 in cadmium responses - Aksoy, Emre (Landes Bioscience, 2013)
Transcriptional and post-transcriptional responses to external iron (Fe) availability are essential for the cellular Fe homeostasis. Fe deficiency strongly induces Fe utilization-related gene expression; however, little is known about the early Fe signaling that regulates expression of a central transcription factor FIT. In Arabidopsis, mutations in RNA polymerase II CTD-phosphatase-like 1 (CPL1) enhance the expression of Fe utilization-related genes including FIT under Fe deficiency. Fe content is significantly increased in the roots and decreased in the shoots of cpl1-2 plants, and root growth of the cpl1-2 mutant shows higher tolerance to Fe deficiency and to toxicity of cadmium (Cd). The cpl1-2 plants accumulate more Cd in the shoots, suggesting that Cd toxicity in the cpl1-2 roots is circumvented by the transport of excess Cd to the shoots. Here we show data suggesting that the root-to-shoot translocation of Cd in cpl1-2 is mediated by yet uncharacterized Cd transport mechanisms.